Curves and Colors: a Journey into Hundertwasser’s Visual Language (diségno, 2025)
This paper offers a critical and original reading of Friedensreich Hundertwasser’s work, focusing on the continuity between his visual language in painting and architecture. Moving beyond symbolic or stylistic interpretations, the analysis introduces the concept of atmospheric drawing: a perceptual grammar in which color, line, and texture do not merely represent but generate multisensory and affective environments. Hundertwasser’s graphic signs –spirals, organic curves, chromatic contrasts– are interpreted as compositional devices that activate emotional responses and structure space, both pictorial and architectural. By comparing specific paintings such as Irinaland over the Balkans with buildings like the Hundertwasserhaus or the Waldspirale, the article demonstrates how drawing operates as a generative process that redefines the relationship between humans, architecture, and nature. The concept of the ‘third skin’ is reexamined as a sensory interface, mediating the boundaries between interiority and landscape. Finally, the paper proposes the idea of visual ecology as a framework for understanding drawing as a critical and environmental practice. In doing so, it positions Hundertwasser’s work as a living laboratory for rethinking the role of drawing, not as a static representation of reality, but as a creative tool for shaping how we perceive, inhabit, and imagine the world.
Keywords: Hundertwasser; visual semiotics; drawing; graphic language; colors